Climate change and major plagues in the Roman period - McDonald, B (2020)
This thesis examines the climate of the ancient Mediterranean from the second century BC to the sixth century AD, as well as major outbreaks of disease, with the principal aim of investigating potential explanations for apparent connections between climate change and the major pandemics of the Roman world. In addition, I consider the influence of the three great Roman “plagues” on society, assessing whether their effects, or lack thereof, are as apparent as scholars suggest.